Current demand balancing a technique for minimization of current surge in high performance clock-gated microprocessors. - Yiran Chen (IEEE Transactions on VLSI systems)
We propose an integrated architectural and physical planning approach to minimize the current surge in high-performance clock-gated microprocessors. In our approach, we use priority assignment optimization (PAO) and dynamic functional unit (FU) selection (DFS) to balance current demand in the floorplan. Two complementary methods-FU ordering with submodule design and issue pattern management-are also proposed to enhance the above techniques. Experimental results show that at the 0.18-μm technology node, the PAO can reduce the peak noise by 11.75% and consequently, the decoupling capacitance (Decap) requirement by 24.22% without any degradation in instructions per cycle (IPC). Moreover, an enhanced DFS reduces the peak noise by 13.39% as well as Decap requirement by 29.58%. Experiments at the 90-nm technology node show that our methodology can further reduce the peak noise and the Decap requirement by 16.57% and 44.85% with PAO, or 18.16% and 47.58% with DFS. We also show that our approach does not increase the clock period for 0.18-μm technology and beyond.